Characteristics of adult chum salmon Oncorhynchus keta from the commercial stock at Iturup Island in 2024 - A. N. Elnikov; O. V. Zelennikov (Известия ТИНРО, 2025)
Spawners of chum salmon Oncorhynchus keta were examined in the basins of Prostor and Kurilsky Bays (Iturup Island, Kuril Islands) from September 23 to November 2, 2024. The portion of females naturally increased during the spawning run and was 43.3 %, on average. The fish aged 3+ clearly dominated, their portion was on average 83.7 % in the Prostor Bay and 90.9 % in the Kurilsky Bay, however, the portion of fish with age 2+ increased during the run. The females and males aged 3+ weighted 2.28 and 2.44 kg, on average, respectively, that was less than the weight of chum salmon spawners in this area over the previous 10 years.